Diversity of Moss Species (Bryophyta) In Senggani Ravine Tourism Area, Tulungagung Regency - Kartikasari, Desi; Anon Widodo, Gading; Habibah, Nur; Zahratul Asna, Rakhmi (Universitas Negeri Surabaya, 2023)
Moss plants (Bryophyta) are found in every habitat, and their presence in an ecosystem is controlled by environmental circumstances. The Senggani Ravine tourism area is a popular tourist attraction comprising a pine forest with extensive moss communities. This work aimed to assess the diversity of mosses (Bryophyta) in the Senggani Ravine tourism area for the first time. In June 2022, exploratory descriptive research of moss diversity was undertaken by a free walk around the Senggani Ravine tourism area from a predetermined position point (purposive sampling) using observation, documentation, literature study, and measurement of abiotic elements for data collection. Based on the results, twenty species of mosses were identified and can be divided into four classes, namely the Bryopsida, Polytrichopsida, Jungermanniopsida, and Marchantiopsida. The species identified were Barbulla indica, Fissidens purpusillus, Fissidens biformis, Fissidens biformis, Octoblepharum albidum, Rhizonium punctatum, Mnium hornum, Philonotis marchica, Fontinalis antipyretica, Hypnum cupressiform, Polytrichastrum formosum, Lejeunea flava, Lejeunea cavifolia, Bazzania prareupta, Bazzania vittata, Riccia junghuhniana, Marchantia emarginata, Marchantia polymorpha, Dumortiera hirsuta, and Lunularia cruciate. Abiotic factor measurements revealed that zone 3, which has a soil pH of 6, an air temperature of 24.1 C°, an 84% humidity level, and 200 Cd of light cm-1, is the most favorable area for moss growth. We can infer that the Senggani Ravine tourism area is still primarily undisturbed because the moss flora is still quite diverse and varied.